The Analysis of Two BDNF Polymorphisms G196A/C270T in Chinese Sporadic Amyotrophic Lateral Sclerosis - Xu, Lianping; Tian, Danyang; Li, Jiao; Chen, Lu; Tang, Lu; Fan, Dongsheng (Frontiers in Aging Neuroscience, 2017)
ABSTRACT Amyotrophic lateral sclerosis (ALS) is an ethnically heterogeneous motor neuron disease that results from the selective death of motor neurons in the brain and spinal cord. Brain-derived neurotrophic factor (BDNF) is widely distributed across the central and peripheral nervous systems and plays neurotrophic and other physiological roles in various brain regions. Alterations of neurotrophin availability have been proposed as a pathogenic mechanism underlying ALS neurodegeneration. Several genetic studies have shown a significant association between schizophrenia, Alzheimer’s disease, and Parkinson’s disease and certain BDNF polymorphisms, specifically G196A (rs6265) and C270T (rs56164415). However, the relationship between the G196A and C270T polymorphisms and ALS has never been investigated. We hypothesized that sporadic ALS (sALS) and disease susceptibility could arise due to BDNF polymorphisms and investigated the relationship between ALS and the BDNF polymorphisms G196A and C270T in a large Chinese cohort. We demonstrate that the frequency of the CT genotype and of the C270T T allele was significantly higher in the ALS group than in controls, although G196A was not associated with sALS. These data provide the first demonstration that the BDNF C270T polymorphism may be a candidate susceptibility locus for sALS, at least in Han Chinese.